INNOVATION AND ENTREPRENEURSHIP AS PILLARS OF ECONOMIC DEVELOPMENT: A REVIEW OF THE LITERATURE AND ITS IMPLICATIONS FOR SOCIETY - Benediktus Rolando; Robby Cahyadi; Silvia Ekasari (JOURNAL OF COMMUNITY DEDICATION, 2023)
Innovation and entrepreneurship are key elements of economic development. The focus is on creating new ideas, technologies and business processes that can be more efficient and productive. Innovation means creating creative solutions that can be initiated, developed and marketed according to changing market needs, while entrepreneurship refers to the process of starting and advancing entrepreneurial life by managing new companies, creating labour, bringing economic diversification in a sustainable manner. The study conducted in this research uses the literature research method. The results show that Innovation and entrepreneurship have several macro effects that impact the economy. At the micro level, first of all, they create new jobs, which helps to lower the unemployment rate and improve social welfare. Secondly, innovation and entrepreneurship serve as an important way of diversifying the economy. This in turn helps lower the level of dependence on a single sector and increases the resilience of the economy to external shocks. Third, a business culture shaped by entrepreneurial spirit fosters economic dynamism and a sustainable innovative ecosystem.